Comportamiento entre los países colombia y méxico, conforme a la facilidad de hacer negocios, teniendo como referente los resultados del indicador DOING BUSINESS-2019 (2022)
Given that Colombia has been presenting a low rating in the Doing Business ranking compared to previous years; It is taken as a reference and justification to propose an investigation with a documentary approach, whose objective was focused on comparing the ease of Doing Business presented in the countries of Colombia and México. The latter market is chosen, because it is the country with the most business-friendly system, above Colombia, leading these differences to the identification of advantages and disadvantages, which may be occurring in business participation in business. As a method, it begins by describing the importance of the Doing Business indicator, to go on to highlight the general conditions of the business environment for the cases of Colombia and Mexico, taking into account the results of the variables associated with the Doing Business-2019 indicator and end with the differences in the ease of doing business according to the results of the general conditions of the business environment leading to the identification of advantages and disadvantages in business relationships, culminating in the analysis of the PEST Matrix instrument and drawing conclusions as to which are both endogenous and exogenous that stood out from this comparison; concluding that Mexico surpasses Colombia by 7 positions, showing that the procedures, costs and time used in each of the sub-indicators are high and directly impact the performance of the economies in terms of the ease of doing business. Therefore, the elimination of unnecessary procedures is recommended, so this can reduce costs for the creation of a business at the same time, or that they can be presented together to make them clearer, thereby facilitating competitiveness and growth.